Desempenho e custo horário de um trator agrícola utilizando biocombustível extraído do óleo de soja - Ströher, Gisiane July (2016)
The use of the agricultural mechanization became indispensable for the development of agriculture, whether in small or large properties, in conventional or agro ecological bases. The energy used to move the engines, in the majority it is extracted from petroleum reserves, and it is known that these are limited and will become finite in the near future. Besides this difficulty, other obstacle for a sustainable production is the pollution generated by the use of those fossil fuels. Thus, the biofuel can appear as an alternative source to the fossil fuels, going against the agro ecological principles. The biofuel can be produced from vegetable oil, being biodegradable and of renewable source. Therefore, this study had as goal to compare consumption of a tractor of diesel cycle fed with 100% of commercial diesel oil (OV0) and with the mixture OV20, composed of 80% of commercial diesel oil more 20% of vegetable oil of soybean (OV100) in field operations, working without load and also coupled to a clearing saws of direct transmission, in operations of preparation of the soil; to determine the indexes of slippage of the tractor and designate the tractor hourly labor cost with the use of those fuels. The test was led on the dependences of Experimental Farm of Iguatemi of the State University of Maringa (PR), with randomized blocks design, in factorial outline 2x3x2 with four replications. As result, it was found that: the tractor fed with the mixture composed of 80% of commercial diesel oil B S10 (OV0) and 20% of soy vegetable oil (OV20), it presented higher consumption than when it was just fed only with commercial diesel oil B S10. In both the fuels tested, the consumption was higher when the tractor operated with load, independently of the speed; the tested speeds showed no significant difference when the tractor worked fed with the commercial diesel oil B S10 (OV0), for both the work with load or no load. The percentages of slippage are in accordance with the recommended indexes. The tractor fed with the denominated fuel OV20 it presented an hourly cost 8,75% higher than with the tractor using the OVO fuel.